Innovation Capability and Organizational Learning on SME Performance: CRM Mediation and Absorptive Capacity Moderation - Azizah Jannatin Fadhilah; Afifah Assajidah; Afif Aqil; Mega Utami (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of innovation capability and organizational learning on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage (F&B) sector in Bekasi City. Customer Relationship Management (CRM) is used as a mediating variable, while absorptive capacity functions as a moderating variable. The research adopts a quantitative approach with an explanatory research design. Data were collected through a five-point Likert scale questionnaire distributed to 588 F&B MSMEs selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS version 24 to examine direct effects, indirect effects, and moderating effects among variables. The results show that innovation capability and organizational learning have a positive and significant effect on MSME performance. In addition, both innovation capability and organizational learning positively influence CRM, and CRM has a significant effect on MSME performance. These findings confirm that CRM acts as a mediating variable that links innovation capability and organizational learning to MSME performance. Furthermore, the moderating test results indicate that absorptive capacity strengthens the relationship between innovation capability, organizational learning, and MSME performance. Overall, this study demonstrates that MSME performance is not only determined by the ability to innovate and learn, but also by the ability to manage customer relationships and effectively absorb and utilize external knowledge. This research contributes theoretically to the development of strategic management and dynamic capability literature. It also provides practical implications for MSME owners and policymakers in designing sustainable strategies to improve MSME performance.